A framework to measure regional disparities in battery electric vehicle diffusion in Ireland - Sanghamitra Chattopadhyay Mukherjee (University College Dublin, UCD School of Economics, 2021)
This work studies the role of socio-economic and geospatial factors in shaping battery electric vehicle adoption for the case study of Ireland. It provides new insights on the level and timing of likely adoption at scale using a Bass diffusion model combined with a spatial model. The Bass model demonstrates that a country like Ireland may experience peak sales between 2025 and 2030 given current trends, reaching overall uptake levels that are not commensurate with current policy goals, whilst also potentially creating gulfs in regional take-up. The key conclusion from the spatial analysis is that location matters for uptake, through various channels that help or hinder adoption such as resources, information, and policy. Additional investment in public charging infrastructure facilities may also be needed as gaps in coverage exist, especially in rural areas to the West and South-West of the country. Although Ireland enjoys good network coverage overall, this study suggests that more charge points may be needed in some counties and Dublin city and suburbia where the number of charge points is currently disproportionate to a minimum network coverage comparable with the land area, population size, number of private vehicle owners, and travel behaviour. As the urgency for climate action intensifies in the coming decade, our spatio-temporal approach to studying uptake will not only help meet Ireland's socio-ecological vision for the future, but also provide insights and strategies for comparable countries that are similarly placed in terms of electric vehicle adoption.
Keywords: D1; D9; O3; Q4; 330; Battery electric vehicle adoption; spatial analysis; consumer behaviour; Bassdiffusion model; Ireland